A phenotype combining hidradenitis suppurativa with Dowling–Degos disease caused by a founder mutation in PSENEN. (14th February 2018) - Pavlovsky, M.; Sarig, O.; Eskin‐Schwartz, M.; Malchin, N.; Bochner, R.; Mohamad, J.; Gat, A.; Peled, A.; Hafner, A.; Sprecher, E.
Summary: Dowling‐Degos disease is rare genetic disorder that starts to appear during puberty, featuring abnormal skin colouring (pigmentation) most commonly in the folds of the skin, known as flexural areas. Familial hidradenitis suppurativa is also a rare genetic disorder that features recurrent boils in flexural areas. It usually starts to appear around puberty. Sometimes the two disorders co‐exist in the same person. Defects in the same gene, called PSENEN, were recently found in patients who have both hidradenitis suppurativa and Dowling‐Degos. The product of PSENEN is a protein that is a part of a complex named NOTCH that plays an important role in the development of the skin and other organs. Here we report 4 Jewish Ashkenazi families who presented with clinical features characteristic of both disorders. All patients were found to carry the same gene defect in PSENEN, a defect that was never shown before. We checked the area around the gene and found it to be the same in all patients. This means that all patients got the mutation from a common ancestor. In the next step of our research project we wanted to show that defect in PSENEN actually influences NOTCH. We used cells from a patient and compared it to cells from a healthy person. We showed that there is less PSENEN in the cells of the patients, and when we insert a special element inside the cells that makes them glow when NOTCH is active, patient cells glow less than cells from healthy people. In conclusion, in this present study we showed a new genetic defect in PSENEN that can cause two diseases at once: Dowling‐Degos disease and hidradenitis suppurativa. We also show that NOTCH is important in both of these diseases. Abstract : Linked Article: Pavlovsky et al. Br J Dermatol 2018;178 :502–508